Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5812/hepatmon.41564
|View full text |Cite
|
Sign up to set email alerts
|

Liver Illness and Psychiatric Patients

Abstract: Patients with psychiatric disorders are usually more exposed to multiple somatic illnesses, including liver diseases. Specific links are established between psychiatric disorders and alcohol hepatitis, hepatitis B, and hepatitis C in the population as a whole, and specifically in drug abusers. Metabolic syndrome criteria, and associated steatosis or non-alcoholic steato-hepatitis (NASH) are frequent in patients with chronic psychiatric disorders under psychotropic drugs, and should be screened. Some psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 77 publications
4
16
0
1
Order By: Relevance
“…11 Liver dysfunctions may be due to the repeated and long-term exposure to toxic substances (alcohol, tobacco, etc,) in manic patients. 43 Moreover, our results showed that the prevalence of hypothyroidism is 5.1% similar to what is found in the literature, 6,17 while the prevalence of hyperthyroidism was similar to that reported worldwide. 17,44 In fact, the prevalence of hyperthyroidism is not common in BD-I and does not exceed 2%.…”
Section: Discussionsupporting
confidence: 89%
“…11 Liver dysfunctions may be due to the repeated and long-term exposure to toxic substances (alcohol, tobacco, etc,) in manic patients. 43 Moreover, our results showed that the prevalence of hypothyroidism is 5.1% similar to what is found in the literature, 6,17 while the prevalence of hyperthyroidism was similar to that reported worldwide. 17,44 In fact, the prevalence of hyperthyroidism is not common in BD-I and does not exceed 2%.…”
Section: Discussionsupporting
confidence: 89%
“…While the total prevalence of liver disease in patients with psychiatric illness is not fully known [29], the prevalence of MetS in schizophrenic or bipolar patients is remarkably high, ranging from 22 to 42% [30], compared to non-psychiatric control populations (with an estimated prevalence of 15-20%). A recent meta-analysis found patients suffering from severe mental illnesses to have a pooled RR of 1.58 (1.35-1.86) of developing MetS [2].…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…In psychiatric patients, the effects of medication also need to be taken into account, as psychiatric treatments may have specific side effects on the liver. They also contribute greatly to weight gain, and the MetS itself [29]. Moreover, there seems to be an inherent risk of developing MetS in relation to psychiatric illness that is also present in non-treated individuals [2].…”
Section: Pathophysiology Of Nafld/nashmentioning
confidence: 99%
“…In previous studies, not only psychiatric disorders but also cardiac and hepatic diseases were frequently seen. 42 , 43 This suggests that anxiety and stress present in individuals by physiological deterioration are deeply involved as personal factors in drug use, and it cannot be denied that the road to societal reintegration may be closed. These results suggested the need to prevent organ disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that psychotropic drug abuse involved not only mental illness but also various diseases such as gastrointestinal diseases. 42 , 43 Therefore, we speculated that the organ damage was due to the psychotropic drugs taken. However, we could not identify psychotropic drug-specific organ damages.…”
Section: Discussionmentioning
confidence: 99%